STRATEGIA: A REFLECTIVE STRATEGY FORMULATION MODEL FOR DEVELOPING SCHOOL EXCELLENCE THROUGH BLUEPRINT-BASED PLANNING - Purwoko, Lukman Fajar; Hariyati, Nunuk; Mustaji, Mustaji; Wardoyo, Dewie Tri Wijayati; Wulandari, Ayu (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study introduces STRATEGIA (Strategic Reflective Action for Growth and Institutional Advantage), a reflective strategy formulation model designed to support schools in developing context-sensitive and strength-based strategic blueprints for institutional excellence. Method: Employing a design-based research approach, the model was piloted with 19 school principals through a structured training program. Data were collected via pre–post surveys, blueprint portfolio analysis, and reflective documentation to evaluate shifts in strategic thinking and planning competence. Results: Findings indicate substantial improvements in participants’ strategic understanding and blueprint development, with score increases ranging from 24% to 53%. Participants rated the model as clear, relevant, and practically applicable in the context of school planning. Novelty: STRATEGIA is distinguished by its integration of Appreciative Inquiry, Resource-Based View (VRIO), SOAR, Organizational DNA, PESTEL, and stakeholder mapping into a five-stage reflective process—Reflective Discovery, Signature Formulation, Strategic Visualization, Roadmap Development, and First-Year Strategic Initiatives. This innovative combination provides a practical and scalable planning framework that is rooted in institutional identity, offering a novel contribution to strategic leadership development in educational settings.